ABOUT THE DEVELOPMENT OF MALE GAMETOPHYTE OF FRUIT TREES (Proceedings of the YSU B: Chemical and Biological Sciences, 2003)
By the test of determination of sterility of pollen grains is investigated the quality of male gametophyte of some species of fruit trees in the zone of Armenian nuclear power-station, about 30 km from ANPS in the zone of Noragygh village. In the population of investigated examples different formation of gametophyte generation is detected. The genotypes with high and low-moderate degrees of microgametophytes defects are isolated.
Keywords: sterility of pollen grains; gametophyte; Armenian nuclear power-station